2021
DOI: 10.33365/jorle.v2i1.906
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Level and Primary Causes of Public Speaking Anxiety Among English Department Students

Abstract: English public speaking anxiety is a crucial issue experienced by students and it needs to be coped with acknowledging the importance of public speaking proficiency concerning today's demands. As EFL students, many studies have found that they encountered a considerable level of public speaking anxiety in which significantly affects their speaking quality. Therefore, measuring students' public speaking anxiety is essential since it can help both the students and teachers to know the level and primary causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In addition, results of their research describe that the low selfconfidence factor accepted the highest average attended by fear of bad evaluation and communication apprehension element. Other studies conducted by Alnahidh and Altalhab [32] , and Sugiyati and Indriani [33] found that the level of moderate in Foreign Language Anxiety Scale of participants in English Class. Any time, when they performed speaking in the class, they already dealt with the anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, results of their research describe that the low selfconfidence factor accepted the highest average attended by fear of bad evaluation and communication apprehension element. Other studies conducted by Alnahidh and Altalhab [32] , and Sugiyati and Indriani [33] found that the level of moderate in Foreign Language Anxiety Scale of participants in English Class. Any time, when they performed speaking in the class, they already dealt with the anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…The findings show that majority of students encountered a medium level of anxiety were similar to previous research done by Faizah and Tuan (2021), Sim et al (2020), Hidayoza et al (2019 and Sitti Kurniawanti (2017). In addition, Melouah (2013) expressed the reason for moderate level of speaking anxiety among students due to low proficiency in speaking English (as cited in Sugiyati and Indriani, 2021). Thus, an average level of speaking anxiety can act as a motivational factor for the learners' to further improve their proficiency.…”
Section: Findings Level Of Public Speaking Anxiety Among Uitm Shah Alam Undergraduatesmentioning
confidence: 99%
“…A study in Malaysia reported that it was found that female and male students experienced anxiety when they were faced with debating activities which was caused by a lack of critical thinking skills (Anthony, Othman & Ismail, 2018). Another study also stated that many of the students experienced medium anxiety when they had to speak publicly which was caused by fear of negative evaluations from lecturers (Sugiyati & Indriani, 2021). In Nila's description, she felt that the criteria for speaking debate require those who can deliver arguments critically and firmly.…”
Section: Steadiness/fear In Making and Delivering An Argumentmentioning
confidence: 99%